2019
DOI: 10.1038/s41598-019-53598-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of thermographic characteristics of the hands and wrists of rheumatoid arthritis patients and healthy controls

Abstract: Thermal imaging has been applied to detect possible temperature variations in various rheumatic disorders. This study sought to determine whether rheumatoid arthritis (RA) patients without active synovitis in their hands exhibit different baseline thermographic patterns of the fingers and palms when compared to healthy individuals. Data from 31 RA patients were compared to that of 51 healthy controls. The RA patients were recruited upon confirmed absence of synovitis by clinical examination and musculoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…Our results have clearly shown that RA feet without active synovitis exhibit higher temperatures than healthy individuals. These results concur with Gatt et al [ 11 ], who explored joints of the hands and fingers of RA subjects without inflammation and have thus likewise set a baseline for normative RA thermal characteristics of the hands. A recent paper has also found significant differences in the temperature of feet between RA participants with inflammation and healthy participants, however it should be noted that their methodology differed somewhat to this study in that they analyzed temperatures through a dorsal approach [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results have clearly shown that RA feet without active synovitis exhibit higher temperatures than healthy individuals. These results concur with Gatt et al [ 11 ], who explored joints of the hands and fingers of RA subjects without inflammation and have thus likewise set a baseline for normative RA thermal characteristics of the hands. A recent paper has also found significant differences in the temperature of feet between RA participants with inflammation and healthy participants, however it should be noted that their methodology differed somewhat to this study in that they analyzed temperatures through a dorsal approach [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…The authors postulate that one cannot apply thermography to detect joint inflammation in RA when the baseline data pertaining to RA itself is unknown. As has been demonstrated [ 11 ], patients with RA may exhibit changes in thermographic patterns even in the absence of active inflammation. Hence the need to perform this same research to characterize thermal patterns in the feet of RA patients without active inflammation becomes very clear.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Based on this evidence, it has been suggested that IRT might have an important role in assessing large and medium joints, lacking effectiveness in the context of small joints. 20,21,33,39 Apart from the diagnostic value of IRT discussed above, its prognostic potential to conduct patient follow-up and/or assess treatment outcomes has been also emphasized by others. IRT is an useful and objective supplementary method to support capacity evaluations to perform work-related activities.…”
Section: Gratt and Sicklesmentioning
confidence: 99%